Analysis of the impact of the public service mal on increasing the number of NIBs in Serang City - Wicaksono, Angga; Sudrajat, Imam; Khoir, Tubagus Gemilang; Wahyudi, Wahyudi (Jurnal Mantik, 2024)
This study aims to determine the impact of the presence of Public Service Mals on the increase in the number of Business Identification Numbers (NIB) in Serang City. To find out how much impact the presence of MPP has, the authors compared the data in 2022 with 2023. This study used a qualitative descriptive method with an inductive approach. The type and source of data used is secondary data. The result of this study is the number of NIBs issued after the presence of MPP in 2023 by comparing data before the inauguration of MPP in 2022. In 2022, there are 5,529 Micro Small Enterprises that have NIB. 2023, after the inauguration of the Serang City Public Service Mal, there will be a significant increase of 206.31% or an increase of 5,878 to 11,407 micro-small enterprises with NIB. Meanwhile, in 2022, 67 Non-MSEs have NIB; in 2023, it will decrease by -34.32% or 44 to only 23 Non-MSEs with NIB. The increase in NIB in 2023 is due to the large number of business actors interested in experiencing the comfort and ease of service at Serang City Public Service Mal